Alterations of Heartbeat Evoked Magnetic Fields Induced by Sounds of Disgust - Kato, Yutaka; Takei, Yuichi; Umeda, Satoshi; Mimura, Masaru; Fukuda, Masato (Frontiers in Psychiatry, 2020)
The majority of the models of emotional processing attribute subjective emotional feelings to physiological changes in the internal milieu, which are sensed by the interoceptive system. These physiological reactions occur via the autonomic nervous system, and give rise to alterations in body-mind interactions that are characterized by heartbeat evoked magnetic fields (HEFs) involving brain regions associated with emotional perception. The current study used magnetoencephalography (MEG) to examine regional cortical activity and connectivity changes in HEFs provoked by the emotion of disgust. MEG results from 39 healthy subjects (22 female) revealed that passively listening to sounds of disgust elicited right insular cortical activity and enhancement of cortical connectivity between the right anterior ventral insular cortex and left ventromedial prefrontal cortex, demonstrated by phase lag indexes in the beta frequency range. Furthermore, inter-trial coherence increased at 19 Hz and 23 Hz, and decreased at 14 Hz, which highlights the involvement of low beta oscillations in emotional processing. As these results were based on spontaneously triggered bioelectrical signals, more indigenous and induced signals were extracted with a block designed experiment. The insular cortices play an important role in emotional regulation and perception as the main cortical target for signals with interoceptive information, providing direct substrates of emotional feelings. The current results provide a novel insight into frequency properties of emotional processing, and suggest that emotional arousal evoked by listening to sounds of disgust partially impact the autonomic nervous system, altering HEFs via connectivity changes in the right anterior ventral insular cortex and left ventromedial prefrontal cortex.